Influence of fruit size on the storability of mango (Mangifera indica L.) fruits - Ahmed, M; Abubakar, M S; Muhamman, M A (Journal of Postharvest Technology, 2019)
It is estimated that huge amount of money is lost annually due to inappropriate grading, sizing and postharvest management practices of mango fruits produced in Nigeria. Thus, the need for this work which aimed at determining the effects of harvested fruit size on the storability of fresh mango fruits. The experiment consisted of two harvested fruit sizes: big and small that were laid in Completely Randomised Design (CRD), data were analysed using Student’s T-test. The effects of harvested fruit size on mango fruits percentage change in diameter, texture, percentage weight loss, skin colour changes and rate of deterioration, percentage deterioration and marketability were observed. The fruits were all packed and placed in cool dry room at an ambient temperature of 33 ± 3 °C and relative humidity of 48 ± 3%. Results revealed that big harvested fruit size had better skin texture and marketability than small fruits. The study therefore concludes that harvested fruit size had significant effect on the storability of mango fruit and the best harvested fruit size for storage and marketability purposes is the big size. Thus, big mango fruits size should be selected for long transit, storage and marketability.